Loyalty : NOMOS LIV. - Levinson, Sanford (NOMOS - American Society for Political and Legal Philosophy., 2013)
Few topics are more ubiquitous in everyday life and, at the same time, more controversial in practice, than that of one's moral obligation to loyalty. Featuring essays by scholars working in a variety of subjects from law to psychology, Loyalty presents diverse perspectives on dilemmas posed by potential conflicts between loyalties to specific institutions or professional roles and more universalistic conceptions of moral duty. The volume begins with a philosophical exploration of theories of loyalty, both Eastern and Western, then moves to examine several problematic situations in which loyal.